Spontaneous biloma manifesting with massive upper gastrointestinal bleed: case report - Kumar, Vipan; Bhuria, Dinesh; Bhargava, Venu M.; Gupta, Rajesh (International Surgery Journal, 2023)
Spontaneous biloma is a rare non-traumatic lesion in which the extrahepatic or intrahepatic bile duct perforates spontaneously with no discernable cause. We present a case of spontaneous biloma in a 68 years old male patient with cholelithiasis and concurrent choledocholithiasis, who presented with acute severe cholangitis. There was no history of abdominal surgery, instrumentation, or trauma in the past. Initial ultrasonography (USG) abdomen showed central intrahepatic dilation, cholelithiasis, and choledocholithiasis. A sizeable hypoechoic lesion with few internal septations was present adjacent to the left lobe of the liver, with USG suspicion of a hydatid cyst. The lesion was abutting and displacing the stomach anteromedially. The patient had an acute renal failure with hemodynamic instability at presentation. The patient was managed with emergency endoscopic drainage under ultrasound guidance and improved after that. On the fourth day, after endoscopic drainage, the patient had a massive upper gastrointestinal (UGI) bleed due to erosion and pressure necrosis of the gastric wall due to biloma. The patient was managed successfully with sleeve gastrectomy and de-roofing of the cyst.